Application of Social Media Twitter as a Strategy for Government’s Transparency: Study on #Kemala Jateng Program (Forum Ilmu Sosial, 2020)
Media social helps and supports society to do their activities associated with interaction among them, such as government activity to create transparency in informatics. This development shows that social media become inseparable resource with great impacts. One of the social medias that is being used by government is Twitter that gives features like uploading pictures, making link or hashtag. This study is focused on the strategy of the government of Central Java province uses Twitter as media social by cooperating with Twitter Indonesia. The government of Central Java launces Twitter Kemala (Kelola Melantas Layanan) as a tool to optimized social media to increase the quality of public services in order to accommodate the society’s interests. Through hashtag #KemalaJateng, the people of Central Java can send their ideas, complains, supports and questions which will be directly responded and reported by the related agencies in the government of Central Java. The purpose of this study is to understand the strategy of the government of Central Java optimizing social media, Twitter, to carry out the obligation as public bodies according UU No. 14, 2008 about public information transparency. In this study the descriptive qualitative method was used in which Communication and Informatics Agency of Central Java and Twitter of Central Java province account was the subject of this study. The result shows that the government of Central Java able to optimized the Twitter Kemala Jateng by responding actively and quickly as their strategy to create good governance according the law.